Complete mitochondrial genome organization of Schizothorax labiatus (McClelland, 1842). (2nd November 2015) - Sahoo, Prabhati Kumari; Goel, Chirag; Bhat, Farooz A.; Balkhi, M. H.; Barat, Ashoktaru
Abstract: The complete mitochondrial genome of Schizothorax labiatus, an endemic coldwater fish of Himalayas was determined for the first time. The genome is 16, 582 bp in length and consists of 13 protein coding genes, 22 tRNAs, 2rRNA genes and one putative control region. The gene organization and its order were similar to other vertebrates. The overall base composition was; A: 29.8%, G: 17.7%, C 27%, T 25.5%, A + T content 55.3% and the G + C content 44.7%. The control region was also consisted of a microsatellite locus (TA)12 between 16, 467 and 16, 490 bp. The present study will provide the rationale for the management and conservation of S. labiatus .